2020
DOI: 10.1039/d0cy01356k
|View full text |Cite
|
Sign up to set email alerts
|

Recent progress in the direct synthesis of γ-valerolactone from biomass-derived sugars catalyzed by RANEY® Ni–Sn alloy supported on aluminium hydroxide

Abstract: The direct synthesis of γ–valerolactone (GVL) from biomass-derived sugars (e.g., cellobiose, sucrose, glucose, and fructose) using Raney nickel-tin alloy supported on aluminium hydroxide (RNi–Sn(x)/AlOH; x is loading amount of Sn)...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 58 publications
0
6
0
Order By: Relevance
“…The highest yield (65%) could be obtained at 245 °C under 6 MPa of H 2 . Rodiansono et al reported that it was possible to directly transform biomass-derived sugars to γ-valerolactone (GVL) using Raney Ni–Sn alloy supported on aluminum hydroxide …”
Section: Raney Ni For Biomass Conversionmentioning
confidence: 95%
“…The highest yield (65%) could be obtained at 245 °C under 6 MPa of H 2 . Rodiansono et al reported that it was possible to directly transform biomass-derived sugars to γ-valerolactone (GVL) using Raney Ni–Sn alloy supported on aluminum hydroxide …”
Section: Raney Ni For Biomass Conversionmentioning
confidence: 95%
“… 48 These results also can be rationalised to the fact that RNi–Sn(3.0)/AA has higher Ni/Sn molar ratio than that of RNi–Sn(1.4)/AA, which means RNi–Sn(3.0)/AA has higher metallic Ni (Ni 0 ) concentration on the outer surface, higher activity to hydrogenate than to hydrolyze-hydrogenate the C C bond of FFalc. 45 Consequently, hydrogenation of C C bond of FFalc will take place rapidly, leading to relatively high yield of THFalc, on the other hand yield of 1,4-PeD decreased oppositely ( Fig. 2(a) ).…”
Section: Resultsmentioning
confidence: 96%
“…S5 and S6, in the ESI †). 45 A great portion of Ni 3 Sn 2 alloy phases and less extent of metallic nickel (Ni 0 ) in the bimetallic Ni-Sn alloy catalyst has been proven by theoretical studies or catalytic reactions to play a pivotal role for the high chemoselectivity in the hydrogenation of unsaturated carbonyl compound, 41,46 substituted aromatic nitro compounds, 47 or direct synthesis of hydroxy-ketones from cellulose. 48 These results also can be rationalised to the fact that RNi-Sn(3.0)/AA has higher Ni/Sn molar ratio than that of RNi-Sn(1.4)/AA, which means RNi-Sn(3.0)/AA has higher metallic Ni (Ni 0 ) concentration on the outer surface, higher activity to hydrogenate than to hydrolyze-hydrogenate the C]C bond of FFalc.…”
Section: Catalyst Characterisationmentioning
confidence: 99%
“…Raney®Ni/AlOH (it was obtained from alkali leaching of Raney Ni-Al alloy according to Petro`s protocol [29]) was mixed with a solution that contained 0.45 mmol SnCl2.2H2O at room temperature and stirred for 2 h. The mixture was placed into a sealed-Teflon autoclave reactor for the hydrothermal treatment at 423 K for 2 h. The resulting precipitate was filtered, washed with distilled water and ethanol, and dried under vacuum overnight then the as-prepared Ni-Sn(1.4)/AlOH was produced. The as-prepared Ni-Sn(1.4)/AlOH sample then was reduced with H2 gas at 573, 673, 773, 873 K for 1.5 h and Ni-Sn(1.4)/AA; AA = amorphous alumina was obtained [30,31].…”
Section: Synthesis Of Supported Ni-sn(14)/aamentioning
confidence: 99%